Impact of flooding on feeding practices of infants and young children in Dhaka, Bangladesh Slums: what are the coping strategies? - Goudet, Sophie M.; Griffiths, Paula L.; Bogin, Barry A.; Selim, Nasima (© 2010 Blackwell Publishing Ltd., 2017)
This article was published in the Maternal and Child Nutrition [ © 2010 Blackwell Publishing Ltd. ] and the definite version is available at : http://dx.doi.org/10.1111/j.1740-8709.2010.00250.x The Journal's website is at: http://onlinelibrary.wiley.com/doi/10.1111/j.1740-8709.2010.00250.x/abstract;jsessionid=9054A557596596E7F96D1D2A81695267.f03t04